Light-triggered CO delivery by a water-soluble and biocompatible manganese photoCORM. Issue 33 (15th July 2016) - Jimenez, Jorge; Chakraborty, Indranil; Carrington, Samantha J.; Mascharak, Pradip K.
Abstract : Careful design of the coligand of the photoCORM [MnBr(CO)3 (pyTAm)] makes it highly stable and soluble in aqueous media and allows light-induced CO release to biological targets. Abstract : The discovery of salutary effects of low doses of carbon monoxide (CO) has spurred interest in designing exogenous molecules that can deliver CO to biological targets under controlled conditions. Herein we report a water-soluble photosensitive manganese carbonyl complex [MnBr(CO)3 (pyTAm)] (2 ) (pyTAm = 2-(pyridyl)imino-triazaadamantane) that can be triggered to release CO upon exposure to visible light. Inclusion of a triazaadamantyl pharmacophore into the coligand of2 improves its stability and solubility in water. Change in the coligand from 2-(pyridyl)imino-triazaadamantane to 2-(pyridyl)iminoadamantane (pyAm) or 2-(quinonyl)imino-triazaadamantane (qyTAm) dramatically alters these desired properties of the photoCORM. In addition to structures and CO-releasing properties of the three analogous complexes1–3 from these three α-diimine ligands, theoretical calculations have been performed to determine the origin of Mn–CO bond labilization upon illumination. Rapid delivery of CO to myoglobin under physiological conditions attests the potential of2 as a biocompatible photoCORM.